Revolution as reformation : Protestant faith in the Age of Revolutions, 1688-1832 - Messer, Peter C. (Religion and American culture (Tuscaloosa, Ala.), 2021)
"Essays that explore how Protestants responded to the opportunities and perils of revolution in the transatlantic age"--